First identification of human adenovirus subtype 21a in Shenzhen, China with high-throughput sequencing - Niu, Dan-dan; Fang, Shi-song; Chen, Zhi-gao; Lv, Qiu-ying; Liu, Ting-ting; Chen, Ni-xuan; Li, Ying-ying; Sun, Ying; Li, Chao; Huang, Shun-wu; Cheng, Yan-peng; Wang, Hong-lin; et al. (Frontiers in Microbiology, 2025)
Human adenovirus type 21 (HAdV-21) is recognized as an important pathogen responsible for acute respiratory infections (ARIs). However, it has been rarely reported and remains poorly characterized to date in China. Outpatient or inpatient children under 14 years old with suspected ARIs were enrolled from two hospitals in Shenzhen from September 2023 to April 2024. Respiratory samples were collected and tested for 22 common respiratory pathogens. A comparative analysis was conducted on the positive proportions of pathogens among different groups. Phylogenetic analysis and amino acid mutation analysis were conducted for HAdV-21 strains. A total of 498 pediatric patients with ARIs were enrolled. There were 366 (73.5%) patients infected with at least one pathogen, and 133 (26.7%) patients co-infected with other pathogens. The most frequently detected pathogens were streptococcus pneumoniae (S. pneumoniae) (30.7%, 153/498), HAdV (16.7%, 83/498), and influenza virus (IFV) (16.5%, 82/498). The positive HAdV-21 strain was sequenced and classified as subtype 21a with genome closely related to other strains found in China, and compared with HAdV-21 strains GZ09107, GZ06109 and BB/201903 in China, Shenzhen-2024-5-ILI-1109 contained only one amino acid insertion mutation in the penton base (GTT, Valine). Phylogenetic analysis for whole genome and major antigen proteins showed that global HAdV-21 strains could be classified into two branches, branch 1 including genotype 21p, branch 2 including subtype 21a and 21b. There were three highly variable regions (HVR3, HVR4, and HVR7) in the hexon protein that varied between two branches. This study initially reported a case of HAdV-21a infection in children in Shenzhen, and the genome showed one amino acid insertion mutation in the penton base compared with reported HAdV-21 strains in China. Our findings may contribute to a better understanding of the molecular epidemiological characteristics of HAdV-21 strains, as well as aid in the development of vaccines.